Exploratory investigation about the behavior of the atrazine herbicide in an Entic Haplustoll soil of the State of Córdoba - Monetti, Mariela (2015)
Fil: Monetti, Mariela. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.